PENGARUH STRUKTUR MODAL, PERPUTARAN MODAL KERJA, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN - Maulana, Yasir; Wijayanti, Tri; Arraniri, Iqbal (Program Studi Akuntansi, Universitas Kuningan, 2023)
The aim of this research is to determine the effect of capital structure, working capital turnover and sales growth on company value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The method used in this research is descriptive and verification methods. The population in this study was 82 companies. The technique used in sampling was purposive sampling technique, resulting in 47 samples with 235 financial report observation data for the 2018-2022 period. The data analysis technique used is panel data regression and hypothesis testing is carried out using the t test and F test. The results of the research show that partially capital structure has an effect on company value, while working capital turnover and sales growth have no effect on company value. Then, simultaneously, capital structure, working capital turnover and sales growth have a positive and significant effect on company value. Keywords: Capital Structure, Working Capital Turnover, Sales Growth, Company Value